2018
DOI: 10.1007/s10554-018-1425-y
|View full text |Cite
|
Sign up to set email alerts
|

Peak left atrial strain as a single measure for the non-invasive assessment of left ventricular filling pressures

Abstract: Echocardiographic assessment of left ventricular (LV) filling pressures is performed using a multi-parametric algorithm. Left atrial (LA) strain was recently found to accurately classify the degree of diastolic dysfunction. We hypothesized that LA strain could be used as a stand-alone marker and sought to identify and test a cutoff, which would accurately detect elevated LV pressures. We studied 76 patients with a spectrum of LV function who underwent same-day echocardiogram and invasive left-heart catheteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 22 publications
(31 reference statements)
3
82
1
3
Order By: Relevance
“…However, the role of LA strain when assessing filling pressures in patients with reduced LVEF is still controversial. Melenovsky et al and Singh et al believed that LASr was less accurate in characterizing LV filling pressures in patients with LV systolic dysfunction than in patients with normal systolic function [12,15]. In contrast, Cameli et al demonstrated that in patients with advanced systolic heart failure, peak atrial longitudinal strain provided a better estimation of LV filling pressures [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of LA strain when assessing filling pressures in patients with reduced LVEF is still controversial. Melenovsky et al and Singh et al believed that LASr was less accurate in characterizing LV filling pressures in patients with LV systolic dysfunction than in patients with normal systolic function [12,15]. In contrast, Cameli et al demonstrated that in patients with advanced systolic heart failure, peak atrial longitudinal strain provided a better estimation of LV filling pressures [36].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that abnormalities in the left atrium have an important effect on the pathophysiology and disease progression of LVDD and heart failure with preserved ejection fraction (HFpEF) [10][11][12][13][14]. Moreover, several studies have implied that left atrial (LA) strain, especially LA reservoir strain (LASr), is clinically useful for the noninvasive assessment of LV filling pressures [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that left atrial strain should be used in diagnosis of LVDD [7]. The previous study indicated that LA strain correlates well with LVEDP, as well as pulmonary capillary wedge pressure [7][8][9][10]. While LASct and LAScd are rarely mentioned in previous studies, cut-off value for LA strain is still undefined by invasive gold reference.…”
Section: Introductionmentioning
confidence: 99%
“…As the primary function of the left atrium is to modulate LV filling ( Figure A ) with its reservoir, conduit, and contractile functions, it is not surprising that functional changes of the left atrium become evident at the earliest stages of LVDD . Moreover, LA function may provide additive value, not only in diagnosing LVDD, but also in grading its severity . In the early stages, the left atrium may compensate for LV diastolic dysfunction through its booster function, but with prolonged LV dysfunction, LA dilatation and eventually LA mechanical failure may occur …”
mentioning
confidence: 99%
“…Left atrial strain globally reflects atrial function, remodelling and distensibility. All these components become progressively more impaired in the setting of chronic LVDD, as in patients with HFpEF . Therefore, LA strain represents the cumulative adverse impact of chronically impaired LV relaxation and end‐diastolic viscoelastic stiffness on the left atrium, which can result in pulmonary venous hypertension during exercise associated with HFpEF.…”
mentioning
confidence: 99%